Preparation method of V-shaped adsorptive starch
By combining high-temperature and high-pressure alcohol method and enzymatic lysis in the preparation of V-type adsorbent starch, the problems of low yield and low preparation efficiency in the prior art are solved, and the efficient preparation of V-type adsorbent starch with excellent adsorption performance is achieved.
Patent Information
- Application Number
- CN202411924403.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
In the existing V-type adsorbable starch preparation methods, the yield is low and the preparation efficiency is not high, which limits its application in industrial production.
V-type adsorbent starch is prepared by first treating high-temperature and high-pressure alcohol method and then enzymatically dissolved. V-type starch is formed by high-temperature and high-pressure alcohol method, and then enzymatically dissolved. Plulanase is used to perform enzymatic reaction, and finally V-type adsorbent starch is obtained through washing and drying.
The water absorption and oil absorption capacity of V-type adsorbent starch is significantly improved, the enzymatic decomposition time is shortened to 2 hours, and the yield rate reaches 80.02-83.71%, which improves the preparation efficiency and reduces the cost.
Smart Images

Figure CN119736356A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing V-type adsorptive starch, and belongs to the technical field of starch modification. Background Art
[0002] Porous starch refers to a modified starch with a honeycomb porous structure obtained by hydrolyzing starch granules at a certain temperature. Due to the hollow pore structure of porous starch, porous starch has a large specific surface area, high porosity, low bulk density, and excellent adsorption properties. The commonly used enzymatic hydrolysis preparation method of porous starch mostly uses native starch as a substrate, which can increase the specific surface area of raw starch and improve its adsorption properties. However, due to its special semi-crystalline particle structure, poor water solubility and adsorption properties, weak binding ability with enzymes, low enzymatic hydrolysis efficiency, and the prepared porous starch has limited adsorption properties and is still insoluble in water, which limits the application scope of traditional porous starch.
[0003] V-type starch is produced by treating with alcohol and water to destroy the original A-type crystal structure, exposing a large number of hydrophilic hydroxyl groups between molecules. The straight-chain starch and ethanol form a V-type complex, showing a V-type crystal structure. The higher concentration of ethanol in the system maintains the basic granular morphology of starch. After high-temperature drying, the V-shaped single helical cavity is retained. When dissolved in water again, the hydrophilic hydroxyl groups inside the starch molecules quickly absorb water, making it soluble in cold water, and the starch granules swell rapidly. The application research of V-type starch is currently focused on the embedding of heat-sensitive functional substances, mainly relying on the embedding effect of the V-shaped single helical cavity. Its loose and porous surface structure also has a certain adsorption effect, but in general, the adsorption performance is average.
[0004] Compared with V-type starch and traditional porous starch, V-type absorptive starch is prepared by enzymatic hydrolysis or acid hydrolysis using V-type starch as raw material. Due to its loose granular structure and V-shaped single helical cavity, V-type starch exposes more hydrophilic hydroxyl groups, so it has higher reactivity and is easily acted upon by enzymes. Therefore, the prepared V-type absorptive starch has excellent adsorption properties and is soluble in cold water. However, the existing technology for preparing V-type porous starch generally has the problem of low yield and unsuitability for industrialization.
[0005] At present, there are examples of using the "two-step method" to prepare V-shaped porous starch, that is, first using a high temperature and high pressure alcohol method to prepare V-shaped granular starch, and then using a composite enzyme (saccharifying enzyme + α-amylase) to treat the V-shaped granular starch to obtain V-shaped porous starch. The V-shaped porous starch prepared by this method has a high oil absorption rate, but the preparation process is cumbersome, the enzymatic hydrolysis time is as long as 6 to 12 hours, and the yield is low, with a maximum of about 60%. Therefore, the efficiency of preparing V-shaped porous starch is low, which limits the application of this method in industrial production.
[0006] There are existing examples of using the "one-pot method" to prepare V-shaped porous starch, that is, adding native starch, alcohol aqueous solution and heat-stable α-amylase simultaneously in a high-temperature and high-pressure reactor to directly prepare V-shaped porous starch by the high-temperature and high-pressure alcohol method. The V-shaped porous starch prepared by this method has high oil absorption and water absorption rates, and the enzymolysis time is short, but the product yield is only about 50%. In order to achieve efficient application in industrial production, the preparation efficiency still needs to be further improved.
[0007] There are existing examples of V-shaped porous starch prepared by "simultaneous treatment of high temperature alcohol method and acid hydrolysis method", that is, while the starch is subjected to high temperature alcohol hydrothermal treatment, hydrochloric acid is added for acid hydrolysis to prepare V-shaped porous starch. The product yield of this method is even lower, only about 45%, and the granular structure is easily lost. Summary of the invention
[0008] Technical issues
[0009] The existing V-type absorptive starch preparation generally has the problem of low yield of V-type absorptive starch. Therefore, it is necessary to provide a simple and efficient method for preparing V-type absorptive starch so that the obtained product has outstanding oil absorption capacity and good crystallinity while the yield needs to be improved.
[0010] Technical Solution
[0011] In order to solve the above problems, the present invention treats starch by first treating it with a high temperature and high pressure alcohol method and then enzymatic hydrolysis to prepare a V-shaped adsorptive starch. The adsorptive starch has the triple effects of V-shaped cavity embedding, surface adsorption and pore adsorption, so its water and oil absorption capacity is significantly improved compared with the porous starch prepared by the traditional method.
[0012] The first object of the present invention is to provide a method for preparing V-type adsorptive starch, wherein the method comprises firstly mixing starch and an ethanol aqueous solution to form a uniform starch emulsion, then adopting a high temperature and high pressure alcohol method to prepare the V-type starch, then cooling the starch, adding pullulanase for enzymolysis, and finally washing and drying the starch to obtain the V-type adsorptive starch.
[0013] In one embodiment of the present invention, the starch includes one or more of ordinary corn starch, rice starch, potato starch, wheat starch, barley starch, and tapioca starch.
[0014] In one embodiment of the present invention, the concentration of ethanol in the ethanol aqueous solution is 35-50%, v / v.
[0015] In one embodiment of the present invention, the mass ratio of starch to ethanol aqueous solution is 1:3-5.
[0016] In one embodiment of the present invention, the reaction temperature in the high temperature and high pressure alcohol method is 70 to 90° C., the stirring rate during the reaction is 300 to 700 r / min, and the reaction time is 20 to 40 min.
[0017] In one embodiment of the present invention, the starch emulsion occupies 25-40% of the volume of the reactor in the high temperature and high pressure alcohol process.
[0018] In one embodiment of the present invention, the temperature after cooling is 55-65°C.
[0019] In one embodiment of the present invention, the added amount of pullulanase is 10-30 U / g starch.
[0020] Preferably, the added amount of pullulanase is 20-25 U / g starch.
[0021] In one embodiment of the present invention, the temperature during enzymatic hydrolysis is 55-65°C.
[0022] In one embodiment of the present invention, the stirring rate during enzymatic hydrolysis is 300-700 r / min.
[0023] Preferably, the stirring rate during enzymatic hydrolysis is 400-600 r / min.
[0024] In one embodiment of the present invention, the enzymatic hydrolysis time is 1-5 hours.
[0025] Preferably, the enzymatic hydrolysis time is 1.5-2.5 h.
[0026] In one embodiment of the present invention, washing is performed using ethanol or an ethanol aqueous solution.
[0027] In one embodiment of the present invention, the method specifically comprises the following steps:
[0028] (1) mixing starch and a 35-50% ethanol aqueous solution and subjecting the mixture to a high temperature and high pressure alcohol treatment, wherein the mass ratio of the starch to the ethanol aqueous solution is 1:3-5;
[0029] (2) After the reaction solution in step (1) is cooled, 10-30 U / g of pullulanase is added for enzymolysis, the temperature during enzymolysis is 55-65° C., the stirring rate is 300-700 r / min, and the time is 1-5 h;
[0030] (3) After the enzymatic hydrolysis reaction is completed, ethanol is added, filtered, washed with an ethanol aqueous solution, dried and crushed to obtain V-type adsorptive starch.
[0031] In one embodiment of the present invention, the addition amount of pullulanase is preferably 20-25 U / g starch, the stirring rate during enzymolysis is preferably 400-600 r / min, and the time is preferably 1.5-2.5 h.
[0032] The invention provides a V-type adsorptive starch prepared by the method.
[0033] The second purpose of the present invention is to apply the V-type absorptive starch prepared above to the fields of food, medicine preparation or environmental protection.
[0034] The third object of the present invention is to provide a powdered fat prepared according to the V-type adsorptive starch prepared above, wherein the preparation method of the powdered fat is as follows: the V-type adsorptive starch and fat are uniformly mixed, and then heated to obtain the powdered fat.
[0035] In one embodiment of the present invention, the oil comprises vegetable oil and / or animal fat.
[0036] In one embodiment of the present invention, the vegetable oil includes one or more of corn oil, sunflower oil, and peanut oil.
[0037] In one embodiment of the present invention, the animal fat is a melted liquid fat, including one or more of lard, mutton fat, and beef tallow.
[0038] In one embodiment of the present invention, the mass ratio of V-type adsorptive starch to oil is 1:1.3-1.4.
[0039] In one embodiment of the present invention, the heating temperature is 65-75°C.
[0040] The invention provides powdered fat prepared by the method.
[0041] The powdered oil provided by the invention is applied in the food field.
[0042] Beneficial Effects
[0043] (1) Efficient preparation: In the preparation process of the present invention, the V-shaped single helical structure of V-shaped starch exposes a large number of hydrophilic hydroxyl groups, which can improve the sensitivity of starch to enzymes and facilitate the enzymatic hydrolysis reaction. At the same time, the loose structure and large specific surface area of V-shaped starch are conducive to improving the enzymatic hydrolysis efficiency. Compared with the existing method for preparing V-shaped porous starch, the present invention can complete the enzymatic hydrolysis in about 2 hours to obtain a product with outstanding adsorption performance, and the enzymatic hydrolysis time is significantly shortened. At the same time, the present invention uses a single enzyme for enzymatic hydrolysis, the enzymatic hydrolysis conditions are easy to determine and convenient to control, and the preparation cost is low.
[0044] (2) High product yield: In the present invention, since the short-chain dextrin by-product of pullulanase hydrolysis can combine with ethanol to form a V-shaped complex and also has a certain adsorption capacity, it can be precipitated by ethanol. Therefore, the final product yield can reach 80.02-83.71%, which is much higher than other methods for preparing V-shaped porous starch.
[0045] (3) Excellent product performance: The present invention first uses high-temperature alcohol hydrothermal treatment to obtain V-type starch with a basic particle structure, high reaction activity, and a V-shaped single helix crystal structure, and then increases the specific surface area and average pore size of the V-type starch through enzymatic hydrolysis, so that the prepared V-type absorptive starch has the triple effects of V-shaped single helix cavity encapsulation, surface adsorption, and pore adsorption, and has excellent oil absorption capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The X-ray diffraction patterns of the V-type absorptive starch, V-type starch and native starch prepared in Example 1 of the present invention and the corresponding relative crystallinity diagram;
[0047] Figure 2 This is the scanning electron microscope image of native starch;
[0048] Figure 3 This is a scanning electron microscope image of V-type starch;
[0049] Figure 4 This is a scanning electron microscope image of the V-type adsorptive starch prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0050] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0051] 1. Test method for oil absorption rate:
[0052] Weigh 1.00g of V-type absorptive starch (mass M1) and place it in a 50ml centrifuge tube (centrifuge tube mass M2), add 10ml soybean oil, stir at 50℃, 200r / min for 30min, centrifuge at 4000r / min, 25℃, centrifuge for 20min, pour out the supernatant, wipe the tube wall, record the total weight of the sediment and the tube as M3. Calculate the oil absorption rate according to the formula.
[0053] Oil absorption rate = (M3-M1-M2) / M1×100%
[0054] 2. Test method for starch crystallinity:
[0055] The crystal structure of the sample was analyzed by X-ray diffractometer, with a scanning angle of 3-36° (2θ) and a scanning speed of 0.05° / s. The relative crystallinity was calculated by MDI JADE software: the ratio of the area of the characteristic peaks of type V crystals (7.8°, 13.5° and 20.8°) or the area of the characteristic peaks of type A crystals (15°, 17°, 18° and 23°) to the total dispersion area. The calculation formula is as follows:
[0056] Relative crystallinity (%) = CDA / TDA × 100
[0057] Where CDA represents the peak area of the characteristic crystalline peak, and TDA represents the total area of all diffraction peaks in the scanning interval.
[0058] 3. Test method of yield
[0059] The weight of the raw material used is recorded as M1, and the weight of the final sample is recorded as M2. The yield is calculated according to the formula:
[0060] Yield = M2 / M1×100%
[0061] 4. Determination of chromaticity
[0062] The chromaticity of powdered oil is measured by a handheld colorimeter. The sample is evenly spread on a petri dish and covered with low reflectivity glass, and calibrated with a white plate before each test. Three readings are taken for each sample, and the sample color is reflected by the CIELAB scale. The L* value represents brightness (0-100), a* represents redness (-) and greenness (+), and b* represents blueness (-) and yellowness (+). The whiteness index (WI) and yellowness index (YI) are calculated using the following formulas:
[0063] WI=L*-3b*
[0064] YI=142.86b* / L*
[0065] The enzymatic activity of pullulanase in the following examples is 1000 U / g.
[0066] Example 1
[0067] Weigh 8g of common corn starch and 32g of 45% (v / v) ethanol aqueous solution in a 100mL blue-capped bottle to start the alcohol hydrothermal reaction. The operating parameters of the blue-capped bottle are: reaction temperature 80°C, stirring rate 500r / min during the reaction, and reaction time 30min. After the reaction is completed, cool down. When the temperature drops to 60°C, add pullulanase (the amount of enzyme added is 20U / g starch) and perform enzymolysis reaction at 60°C for 2h. The stirring rate is 500rpm during the reaction. After the reaction is completed, wash with anhydrous ethanol and 95% ethanol respectively, vacuum filter, dry at 100°C for 2h, crush, and pass through a 100-mesh sieve to obtain V-type adsorptive starch.
[0068] The V-type adsorptive starch has an oil absorption rate of up to 340.11%, a yield of up to 82.08%, and a crystallinity of 13.34%.
[0069] Example 2
[0070] Weigh 8g of common corn starch and 32g of 45% (v / v) ethanol in a 100mL blue-capped bottle to start the alcohol hydrothermal reaction. The operating parameters of the blue-capped bottle are: reaction temperature 80°C, reaction speed 500r / min, reaction time 30min. After the reaction is completed, cool down. When the temperature drops to 60°C, add pullulanase (the amount of enzyme added is 20U / g starch), and perform enzymolysis reaction at 60°C for 2h. The stirring rate during the reaction is 700r / min. After the reaction is completed, wash with anhydrous ethanol and 95% ethanol respectively, vacuum filter, dry at 100°C for 2h, crush, and pass through a 100-mesh sieve to obtain V-type adsorptive starch.
[0071] The V-shaped porous starch has an oil absorption rate of up to 221.45%, a yield of up to 83.23%, and a crystallinity of 11.00%.
[0072] Example 3
[0073] Weigh 8g of common corn starch and 32g of 45% (v / v) ethanol in a 100mL blue-capped bottle to start the alcohol hydrothermal reaction. The operating parameters of the blue-capped bottle are: reaction temperature 80°C, reaction speed 500r / min, reaction time 30min. After the reaction, cool down. When the temperature drops to 60°C, add pullulanase (the amount of enzyme added is 20U / g starch), and perform enzymolysis reaction at 60°C for 5h. The stirring rate during the reaction is 500r / min. After the reaction, wash with anhydrous ethanol and 95% ethanol respectively, vacuum filter, dry at 100°C for 2h, crush, and pass through a 100-mesh sieve to obtain V-type adsorptive starch.
[0074] The V-type adsorptive starch has an oil absorption rate of 126.92%, a yield of 80.02%, and a crystallinity of 9.90%.
[0075] Example 4
[0076] V-type adsorptive starch was prepared by referring to the method of Example 1, except that the amount of pullulanase added was different. 10U / g, 15U / g, 20U / g, 25U / g, and 30U / g starch corresponded to 0.2%, 0.3%, 0.4%, 0.5%, and 0.6% enzyme addition, respectively. The other conditions remained unchanged. The results are shown in Table 1.
[0077] Table 1 Effect of pullulanase dosage on the properties of V-type adsorbent starch
[0078]
[0079] Example 4 investigates the effect of enzyme addition on the adsorption characteristics of V-type absorptive starch. When the enzyme addition amount is 10U / g starch, due to the low enzyme addition amount, the enzymatic hydrolysis of V-type starch is insufficient, and more pore structures are not formed on the surface of starch granules, so the oil absorption rate is not significantly improved. The adsorption effect of V-type absorptive starch prepared when the enzyme addition amount is 20U / g starch is the best. With the subsequent further increase in enzyme addition, the adsorption effect of V-type absorptive starch begins to decline. This is because excessive enzymatic hydrolysis destroys the V-type crystalline structure, causing the formed pore structure to collapse and even leading to starch cleavage. Therefore, the preferred enzyme addition amount range is 15-25U / g starch.
[0080] Example 5
[0081] V-type adsorptive starch was prepared by referring to the method of Example 2, except that the stirring rates during the enzymatic hydrolysis reaction were different, 300 r / min, 400 r / min, 500 r / min, 600 r / min, and 700 r / min, and the other conditions remained unchanged. The results are shown in Table 2.
[0082] Table 2 Effect of stirring rate during enzymatic hydrolysis on the properties of V-type absorptive starch
[0083]
[0084] Example 5 investigates the effect of the stirring rate during the enzymolysis reaction on the adsorption characteristics of V-type absorptive starch. When the stirring rate is below 400r / min, the enzyme is unevenly distributed in the reaction system, the local enzyme concentration is too high, and the substrate concentration rises after excessive enzymolysis and inhibits the enzyme activity. There may be a situation where some holes have not yet been formed, and the hole structure of other parts has collapsed, and the final sample has poor adsorption characteristics. When the stirring rate is 400r / min, the enzyme is evenly distributed, and each part is fully enzymolyzed to form a hole structure. The adsorption of V-type absorptive starch prepared under this condition is the best. When the stirring rate is higher than 400r / min, the enzyme is difficult to combine with the substrate, and the starch cannot be effectively enzymolyzed. The shear stress effect of the high stirring rate may cause changes in the secondary structure of the enzyme and energy dissipation, which may lead to a decrease in enzyme activity, weakened hydrolysis, and no obvious improvement in adsorption performance. Therefore, the preferred stirring rate is 400-600r / min.
[0085] Example 6
[0086] V-type adsorptive starch was prepared by referring to the method of Example 3, except that the enzymatic hydrolysis time was different, 1h, 2h, 3h, 4h, 5h, and the other conditions remained unchanged. The results are shown in Table 3.
[0087] Table 3 Effect of enzymatic hydrolysis time on the properties of V-type adsorbent starch
[0088]
[0089] Example 6 investigates the effect of enzymolysis time on the adsorption characteristics of V-type absorptive starch. When the enzymolysis time is 2h starch, due to the short enzymolysis time, a certain pore structure is formed, but due to the short action time, the oil absorption rate at this time is improved but does not reach the peak value. When the enzymolysis time is extended to 2h, the adsorption effect of the V-type absorptive starch prepared at this time is the best. As the subsequent enzymolysis time continues to extend, the adsorption performance of the V-type absorptive starch begins to decline. This is because excessive enzymolysis destroys the V-type crystalline structure, causing the formed pore structure to collapse and even leading to starch cleavage. Therefore, the preferred enzymolysis time range is 1-3h.
[0090] Example 7
[0091] Accurately weigh 1 g of the V-type adsorptive starch prepared in Example 1 into a mortar, and add 120%, 130%, 140%, 150%, and 160% (w / w) of camellia seed oil relative to the mass of the V-type adsorptive starch, respectively, and evenly dry mix. Wrap the mortar with tin foil to protect it from light, put it in an oven, and heat it at 70°C for 10 min.
[0092] Table 4 Effect of oil addition on chromaticity index of powdered camellia seed oil
[0093]
[0094] As the amount of oil added gradually increases, the whiteness of the powdered oil shows a downward trend, while the yellowness changes in the opposite direction. When the amount of oil added in the early stage is small, there is no obvious change in whiteness and yellowness. This may be because the oil is mainly adsorbed inside the V-shaped absorptive starch, mainly due to the V-shaped cavity embedding and pore adsorption, and the amount of oil retained on the starch surface has no obvious change. When the amount of oil added exceeds 140% and continues to increase, the whiteness decreases significantly and the yellowness increases significantly. This may be because the adsorption of oil inside the starch reaches saturation, and the excess oil is adsorbed on the surface, so the chromaticity changes significantly. When the subsequent oil addition reaches 160%, the surface adsorption also reaches the limit, and the excess oil is free between the starch particles to form lumps, and the powderization degree of the oil is poor. Considering the amount of oil added, chromaticity index and powderization degree, the amount of oil added when preparing powdered camellia oil is finally selected to be 140%.
[0095] Example 8
[0096] Accurately weigh 1 g of the V-type adsorptive starch prepared in Example 1 into a mortar, and evenly dry-mix it with 140% (w / w) of camellia seed oil. Wrap the mortar with tin foil to protect it from light, put it in an oven, and heat it at 50°C, 60°C, 70°C, 80°C, and 90°C for 10 min.
[0097] Table 5 Effect of heating temperature on chromaticity index of powdered camellia oil
[0098]
[0099] As the heating temperature increases, the whiteness of the powdered camellia oil first increases and then decreases, while the yellowness is the opposite. When the heating temperature reaches 70°C, both the whiteness and yellowness reach their maximum values. In the early stage, due to the increase in temperature, the viscosity of the camellia oil is reduced, the movement speed of the oil molecules is accelerated, and the oil is promoted to diffuse into the interior of the V-type absorptive starch. There is less oil retained on the surface of the product, and the color index and powderization degree of the product are better. When the temperature continues to rise, the potential energy between the oil molecules increases and gets rid of the adsorption force of the V-type absorptive starch. The oil molecules originally adsorbed inside the starch move and diffuse to the surface, the surface oil content increases, and the powderization degree and color index of the product decrease. Therefore, 70°C is selected as the heating temperature for preparing powdered camellia oil.
[0100] Comparative Example 9
[0101] Take 1g of common corn starch and mix it evenly with 140% (w / w) camellia oil according to the method of Example 8, wrap the mortar with tin foil to avoid light, put it in an oven and heat it at 70°C for 10 minutes. The starch-oil mixture obtained has serious agglomeration, very low powderization, whiteness of 50.51, yellowness of 20.89 and poor color index.
[0102] Comparative Example 10
[0103] The method of reference example 1 is different in that the enzymolysis step is omitted and V-type starch is prepared by direct high-temperature alcoholization. The specific operation steps are: weigh 8g of common corn starch and 32g of 45% ethanol solution in a blue-capped bottle to start alcohol hydrothermal reaction. The operating parameters of the blue-capped bottle are: reaction temperature 80°C, stirring rate 500r / min during reaction, and reaction time 30min. After the reaction is completed, it is cooled to room temperature, washed with 95% concentration ethanol, vacuum filtered, dried at 100°C for 2h, crushed, and sieved through a 100 mesh sieve to obtain V-type starch. Referring to the method of Example 9 again, it is evenly mixed with 140% (w / w) camellia oil, the mortar is wrapped with tin foil for light protection, put into an oven, and heated at 70°C for 10min. The starch-oil mixture obtained has agglomeration phenomenon, poor powderization, whiteness 50.51, yellowness 20.89, and poor color index.
[0104] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing V-type absorptive starch, characterized in that: The method comprises first mixing starch and ethanol aqueous solution to form a uniform starch emulsion, then adopting a high temperature and high pressure alcohol method to prepare V-type starch, then cooling the starch, then adding pullulanase for enzymolysis, and finally washing and drying the starch to obtain the V-type adsorptive starch. The addition amount of the pullulanase is 10-30 U / g starch; the temperature during the enzymolysis is 55-65° C., the stirring rate is 300-700 r / min, and the time is 1-5 h.
2. The preparation method according to claim 1, characterized in that The starch includes one or more of ordinary corn starch, rice starch, potato starch, wheat starch, barley starch, and tapioca starch.
3. The preparation method according to claim 1, characterized in that: The concentration of ethanol in the ethanol aqueous solution is 35-50%, v / v.
4. The preparation method according to claim 1, characterized in that: The mass ratio of starch to ethanol aqueous solution is 1:3-5.
5. The preparation method according to claim 1, characterized in that: In the high temperature and high pressure alcohol method, the reaction temperature is 70-90°C, the stirring rate is 300-700r / min, and the reaction time is 20-40min.
6. The preparation method according to claim 1, characterized in that: The addition amount of the pullulanase is 20-25U / g starch; the stirring rate during the enzymolysis is 400-600r / min, and the time is 1.5-2.5h.
7. A V-type adsorptive starch, characterized in that: The V-type adsorptive starch is prepared by the method according to any one of claims 1 to 6.
8. Use of the V-type adsorptive starch described in claim 7 in the fields of food, medicine preparation or environmental protection.
9. A powdered fat, characterized in that: The powdered fat is prepared by uniformly mixing the V-type adsorptive starch and fat described in claim 7 and then heating them.
10. The powdered fat according to claim 9, characterized in that: The oils and fats include vegetable oils and / or animal oils and fats; the vegetable oils include one or more of corn oil, sunflower oil, and peanut oil; the animal oils and fats are molten liquid oils and fats, including one or more of lard, sheep fat, and beef tallow; the mass ratio of V-type absorptive starch to oils and fats is 1:1.3-1.4; and the heating temperature is 65-75°C.
Citation Information
Cited By
Preparation method for improving quality of surimi product by using V-type starch-grease inclusion compound
CN120660868A
Preparation method of V-shaped porous starch-grease inclusion compound
CN120884078A